2016
DOI: 10.3389/fnhum.2016.00210
|View full text |Cite
|
Sign up to set email alerts
|

Aesthetic Responses to Exact Fractals Driven by Physical Complexity

Abstract: Fractals are physically complex due to their repetition of patterns at multiple size scales. Whereas the statistical characteristics of the patterns repeat for fractals found in natural objects, computers can generate patterns that repeat exactly. Are these exact fractals processed differently, visually and aesthetically, than their statistical counterparts? We investigated the human aesthetic response to the complexity of exact fractals by manipulating fractal dimensionality, symmetry, recursion, and the numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
66
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 73 publications
6
66
0
Order By: Relevance
“…As such, the defining feature of fractals is self-similarity; a "shape is made of smaller copies of itself…same shape but different size" (Frame et al n.d.). This self-similarity can be identified and quantified by the fractal dimension, D. The equation for fractal dimension, D, is log(N R )/log(1/S R ), where N equals the number of line segments in the pattern, S is the scale factor, and R is the number of recursions of the pattern (Bies et al 2016). For example, a fractal line will have a fractal dimension D score that is between 1.0 and 2.0, whilst a fractal surface will have a D score between 2.0 and 3.0 (Hagerhall et al 2004).…”
Section: Fractal Geometry and Visual Fluencymentioning
confidence: 99%
See 1 more Smart Citation
“…As such, the defining feature of fractals is self-similarity; a "shape is made of smaller copies of itself…same shape but different size" (Frame et al n.d.). This self-similarity can be identified and quantified by the fractal dimension, D. The equation for fractal dimension, D, is log(N R )/log(1/S R ), where N equals the number of line segments in the pattern, S is the scale factor, and R is the number of recursions of the pattern (Bies et al 2016). For example, a fractal line will have a fractal dimension D score that is between 1.0 and 2.0, whilst a fractal surface will have a D score between 2.0 and 3.0 (Hagerhall et al 2004).…”
Section: Fractal Geometry and Visual Fluencymentioning
confidence: 99%
“…Further support for preference for mid-range D scores was found in Bies et al's (2016) study investigating preferences for statistical (fractals that do not repeat exactly but have the same statistical qualities, like those found in nature) or exact (fractal patterns that repeat precisely, created by a computer programme) fractals. For statistical fractals mid-range D scores were preferred, whilst for exact fractals a higher D score was preferred (Bies et al 2016). Interestingly, the mid-range D score of 1.3 is most prevalent in nature (Hagerhall et al 2004(Hagerhall et al , 2015, and found in species-rich habitats (Stevens 2018).…”
Section: Fractal Dimension and Preferencementioning
confidence: 99%
“…The crux of the problem, perhaps, is that D is a general parameter that quantifies complexity in a variety of patterns, whereas β is limited (at least in practice) in its ability to quantify some patterns' complexity. For example, Fourier analysis is poorly suited to describe the complexity of patterns including strange attractors and some line fractals (e.g., dragon fractals and Koch snowflakes), which have been used by vision researchers to study aesthetics [25,31,34,35] and perceived complexity [47]. This provides a strong impetus to convert to D when forming general conclusions.…”
Section: D(mountain Edgementioning
confidence: 99%
“…This is especially important in aesthetics research, where there have been claims of universality in preference for patterns of moderately low complexity [23,26,[34][35][36][37]. To test this hypothesis, it is necessary to be able to translate the units of measurement of researchers who alternately use D [22,25,26,28,29,31,[33][34][35][36][37][38][39][40], β [14,24,30,32,[41][42][43][44][45][46], or, infrequently, both [23,27]. The crux of the problem, perhaps, is that D is a general parameter that quantifies complexity in a variety of patterns, whereas β is limited (at least in practice) in its ability to quantify some patterns' complexity.…”
Section: D(mountain Edgementioning
confidence: 99%
See 1 more Smart Citation